Exploring the therapeutic potential of Thiosemicarbazones-ruthenium (II) complexes: In vitro evaluation - Ahmad, Atif [UNESP]; Graminha, Angelica Ellen [UNESP]; Anam, [UNESP]; Nazir, Afaq; Abe, Saulo H. Mendes; Palmeira-Mello, Marcos V.; Dutra, Jocely L.; Badaro, Wladimir P.D. [UNESP]; Lazzarini, Ana Beatriz [UNESP]; de Moura, Thales Reggiani [UNESP]; Khan, Sabir; Batista, Alzir Azevedo; et al. (Elsevier, 2025)
The global burden of cancer continues to grow, and while standard therapies are extensively used, they are often associated with significant side effects. In this study, four novel ruthenium(II) complexes 1–4 with the general formula [Ru(L)(bipy)(dppb)]PF6 were synthesized, in which L represents vanillin–piperidine thiosemicarbazone derivatives. The ligands were derived from the modification of 3-methoxy-4-[2-(piperidine-1-yl)ethoxy]benzaldehyde (VP) with various thiosemicarbazides: hydrogen (L1), methyl (L2), ethyl (L3), and phenyl (L4). The complexes 1–4 were characterized using UV–Vis spectroscopy, FTIR spectroscopy, elemental analysis, molar conductivity, mass spectrometry, cyclic voltammetry (CV), and NMR techniques, including 1H, 13C, 31P{1H}, HSQC, COSY, and DEPTQ. The in vitro cytotoxicity of the complexes was evaluated using the MTT assay against human lung carcinoma (A549), breast adenocarcinoma (MDA-MB-231), and non-tumorigenic lung (MRC-5) and breast (MCF-10 A) cell lines. All complexes demonstrated decreased IC50 values, suggesting enhanced antitumor activity compared to cisplatin. Among them, complex 4 exhibited better activity against MDA-MB-231 cells (IC50 = 0.99 ± 0.07 μM; SI = 6.66). Morphological evaluation and clonogenic studies showed that complex 4 alters tumor cell structure and inhibits colony proliferation. DNA binding studies, including UV–Vis titration, competitive binding assays (hoechst 33258 and thiazole orange), circular dichroism, and viscosity measurements, suggested that complex 4 interacts with DNA through a weak binding mode. Human serum albumin (HSA) binding studies revealed moderate, spontaneous interaction driven mainly by hydrophobic forces, while agarose gel electrophoresis confirmed concentration-dependent interaction with pBR322 DNA. Overall findings position complex 4 suggest as a promising candidate for further studies in anticancer therapeutics.